Self-organization of silicates on different length scales exemplified by amorphous mesoporous silica and mesoporous zeolite beta using multiammonium surfactants. Issue 35 (2nd June 2020) - Castro, Maria; Losch, Pit; Farès, Christophe; Haouas, Mohamed; Taulelle, Francis; Breynaert, Eric; Kirschhock, Christine; Park, Woojin; Ryoo, Ryong; Schmidt, Wolfgang
Abstract : Reaction gels containing piperidine-based multi-ammonium OSDA yield hierarchical nano-beta zeolite in the presence of aluminum and amorphous mesoporous silica without aluminum, illustrating the highly complex thermodynamic course of zeolite formation. Abstract : In this study the structure directing effect of a gemini-type piperidine-based multi-ammonium surfactant during hydrothermal zeolite synthesis was investigated for two cases: with and without a source of aluminum. The absence of an aluminum source led to the formation of an amorphous mesoporous MCM-48 type silica material, while the presence of aluminum guaranteed the formation of zeolite beta with a hierarchical pore system. The two opposing cases were studied in a time and temperature-dependent manner. The mobility and through space interaction of these large surfactant molecules were studied by liquid state nuclear magnetic resonance (NMR) at a temperature relevant to hydrothermal synthesis (363 K) in pure water and upon addition of an aluminum and silicon source. In the gel state, at different stages of aging and hydrothermal synthesis, low angle X-ray diffraction (XRD) and solid state magic angle spinning nuclear magnetic resonance ( 1 H MAS NMR) spectrometry determined the developing order within the system. At each of these different synthesis steps the respective intermediate materials were calcined. Transmission electron microscopy then allowed closer inspection of the locally developing mesoscopic order, while N2 physisorption was used to follow the evolution of porosity.